The Evolving Landscape of Inquiry: Climate’s Growing Importance in Reconstructing Ancient China - Yitzchak Jaffe; Andrew Womack; Anke Hein (Heritage)
This paper examines the growth of climate change discussions in narratives concerning the development and evolution of human societies in Ancient China over the past two decades. This shift reflects climate’s ascension from a marginal factor to a central player in reconstructions of past human actions and societies. We provide an overview of the expanding research on ancient human–climate interactions in China’s prehistory and early history, emphasizing the increasing importance attached to climate as a major player in the rise and, significantly, the collapse of these societies. Through a meta-analysis of publication trends in the last two decades, we identify the chronological periods and topics where climate has come to be interpreted as having a notable impact.